VIDA PRODUCTIVA Y PRINCIPALES CAUSAS DE DESCARTE DE VACAS HOLSTEIN EN LA CUENCA DE LIMA - Orrego A., Jorge (2003)
Records of 3,100 culled Holstein cows from 10 dairy herds in the Lima valley during the period of 1990 till 1996 were analyzed to determine the age at first calving, number of lactations and length of the productive life as well as the main reasons for culling. In the analysis was considered herd size (>500 cows, 100-500 and <100 cows) and type of farm (private and cooperative). Culling reasons were grouped in problems relating to fertility, udder, feet, calving, emergency, and others. The age at first calving, number of lactations and length of the productive life was 28.6 ± 4.1 months, 3.0 ± 2.0 and 42.9 ± 29.4 months, respectively. Statistical differences due to herd size was not found (p>0.05) with the exception of age at first calving which was lower in herds with more than 500 cows (27.9 m p<0.05). Cows from cooperatives showed an older age at first calving, larger number of lactations and longer productive life (p<0.05). The main reasons for culling were: fertility (52.7%), udder (12.1%), feet (3.0%), calving (3.5%), emergency (8.7%), and others (19.9%).